Celiac Disease: Beyond Diet and Food Awareness - Herrera-Quintana, Lourdes; Navajas-Porras, Beatriz; Vázquez-Lorente, Héctor; Hinojosa-Nogueira, Daniel; Corrales-Borrego, Francisco J.; Lopez-Garzon, Maria; Plaza-Diaz, Julio (MDPI, 2025)
Celiac disease is attributable to a combination of genetic predisposition and exposure to dietary gluten, with immune system involvement. The incidence is increasing globally, and the societal economic burden of celiac disease stretches beyond the cost of gluten-free food. This enteropathy that affects the small intestine has been related to different disorders and comorbidities. Thus, the implications of suffering from this disease are multidimensional and need further consideration. Celiac disease is a serious condition that remains under-recognized, resulting in an increased need for programs for better management. This review aims to summarize the current evidence regarding celiac diseases, with special emphasis on clinical implications, diagnosis, dietary management, socioeconomical aspects, and future perspectives.
Keywords: celiac disease; gluten-free diet; autoimmune disorder; dietary management; autoimmune response; genetic predisposition; health advocacy